KOMPARASI WAKTU PEMROSESAN CPU ANTARA QUANTUM HADAMARD EDGE DETECTION (QHED), CANNY DAN SOBEL DALAM DETEKSI TEPI GAMBAR PERKEBUNAN KELAPA SAWIT - Gultom, Lipantri Mashur; Desi Amirullah (ABEC Indonesia, 2023)
This research was conducted to compare the CPU processing time between Quantum Hadamard Edge Detection (QHED), Canny, and Sobel in Palm Oil Plantation Image Edge Detection with several pixel resolution variations. In QHED, several qubits are used, namely 2, 4, 6, 8, 10, and 12 qubits, while the number of qubits greater than 12 cannot be tested due to the limited RAM memory of the device in this study. The final result of this research proves that QHED can detect the edge of an image with the fastest processing time at the number of qubits 6, while the best image edge detection quality lies at the number of qubits 2. In addition, the comparison of QHED, Canny, and Sobel results in CPU processing time where Canny and Sobel are still faster than QHED, but the quality of image edge detection is still better in QHED.   Keywords: Quantum, Hadamard, Edge Detection